Binary Solvent Additives Treatment Boosts the Efficiency of PTB7:PCBM Polymer Solar Cells to Over 9.5% (Solar RRL 4∕2018). Issue 4 (6th April 2018) - Zheng, Yifan; Wang, Gang; Huang, Di; Kong, Jaemin; Goh, TengHooi; Huang, Wei; Yu, Junsheng; Taylor, André D.
Abstract : In article number1700144, Yifan Zheng, Junsheng Yu and co‐workers demonstrate a high efficiency polymer solar cell (PSC) through introducing a novel binary solvent additive combination of DPE:DIO (diphenyl ether und 1, 8‐diiodoctane). This binary solvent additive system of DPE:DIO combines the influence of DIO on the PC70 BM dispersion together with that of DPE on the PTB7 crystallization. As a result, a significant improvement in power conversion efficiency from 6.96% to over 9.25% has been obtained, which is among the best results reported so far in the literature for PTB7:PC70 BM PSCs. It is believed that this approach could have a broad appeal towards improving PSC performance by separately controlling the morphology of donor crystallinity and fullerene dispersion, thus providing an ideal platform for record‐breaking PSCs in the near future.